2021
DOI: 10.1371/journal.ppat.1009873
|View full text |Cite
|
Sign up to set email alerts
|

EBV latent membrane proteins promote hybrid epithelial-mesenchymal and extreme mesenchymal states of nasopharyngeal carcinoma cells for tumorigenicity

Abstract: EBV-encoded LMPs are consistently detected in nasopharyngeal carcinoma (NPC). Recent evidence suggests potential roles of LMP1 and LMP2A in Epithelial-to-mesenchymal transition (EMT) process in NPC. EMT engages in the generation and maintenance of cancer stem cells (CSCs) and confers on cancer cells increased tumor-initiating and metastatic potential, and higher resistance to anticancer therapies. However, how LMP1 and LMP2A regulate the EMT process to generate cells with different EMT states and its implicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 46 publications
1
19
0
Order By: Relevance
“…These findings are comparable to earlier reports that have shown that EBV maintains a type II latency profile in EBV-associated epithelial cancers, such as EBV-associated gastric carcinoma (EBVaGC) and nasopharyngeal carcinoma 28 . Recent studies have reported that LMP2A and LMP1 play a role in epithelial-to-mesenchymal transition in nasopharyngeal carcinoma, thereby, playing a critical role in the onset of cancer 30 , and IHC expression of LMP1 of EBV has been recently reported in the prostate carcinoma samples 31 . Although BZLF1 is an intermediate early gene, few studies have reported its crucial role in establishing and regulating the EBV latency in the host cells 32 , 33 .…”
Section: Discussionmentioning
confidence: 99%
“…These findings are comparable to earlier reports that have shown that EBV maintains a type II latency profile in EBV-associated epithelial cancers, such as EBV-associated gastric carcinoma (EBVaGC) and nasopharyngeal carcinoma 28 . Recent studies have reported that LMP2A and LMP1 play a role in epithelial-to-mesenchymal transition in nasopharyngeal carcinoma, thereby, playing a critical role in the onset of cancer 30 , and IHC expression of LMP1 of EBV has been recently reported in the prostate carcinoma samples 31 . Although BZLF1 is an intermediate early gene, few studies have reported its crucial role in establishing and regulating the EBV latency in the host cells 32 , 33 .…”
Section: Discussionmentioning
confidence: 99%
“…VM, defined by PAS + /CD34 − staining, are tube-like structures that imitate the function of endothelial blood vessels. VM has been described in NPC ( 30 ) and associated with rapid disease progression and poor patient outcomes ( 10 ). Epstein–Barr virus (EBV), plays a crucial role in NPC malignant behaviors, which is also associated with VM formation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, as epithelial or carcinoma cells progress toward high-grade malignancy, they often activate epithelial-to-mesenchymal transition (EMT). It has been reported recently that in breast cancer and nasopharyngeal carcinoma, the cells residing in intermediate hybrid E/M (baring both epithelial and mesenchymal cell markers) state along the epithelial-to-mesenchymal spectrum exhibit the highest tumorigenicity [ 20 , 21 ]. Therefore, it is likely that acquisition of a hybrid E/M state, regardless of MEndT or EMT process, is essential for tumorigenicity of both carcinomas and sarcomas.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, MEndT, like its reverse process EndMT, is not a binary switch but a dynamic transition, which generates many intermediate phenotypic states arrayed along the mesenchymal (M)-to-endothelial (E) spectrum including mesenchymal-like (M), endothelial-like (E), and hybrid M/E states. Studies suggested that tumor cells staying in different stages have different roles in tumor progression [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%